Bidirectional DC-DC converter with high frequency isolation for V2G applications - Vitor Sobrado (2013)
This paper presents the topological solution of dual active bridge (DAB) with phase shift control for a bidirectional DC-DC converter. This converter typically integrates systems for vehicle to grid (V2G) and vehicle to grid (G2V) applications. About DAB topology are illustrated the key aspects of its operation also the condition of zero voltage switch (ZVS). Experimental results allow to validate their correct operation in applications of V2G and G2V, bidirectional transit of energy.